Vibration test and analysis of mini-tiller - Guo, Li; Jian, Chen; Hangjia, Xie; Shimeng, Wang (International Journal of Agricultural and Biological Engineering, 2016)
Intense vibration happens at the handle of the mini-tillers that abundantly used in mountainous and hilly areas of southwest China. It is absolutely essential to probe into the vibration characteristics and factors why handle of the tiller vibrates violently. Therefore, the vibration acceleration signals of a mini-tiller’s handle and engine cover were tested under the following four conditions: the engine being idle, racing at medium and high speeds, and the tiller working in the field with high engine speed. The signals were processed by means of the time domain eigenvalue analysis and the frequency spectrum analysis. The results showed that when the tiller was under static condition, with increase of the engine speed, the handle vibration decreased in the vertical direction, increased in the fore-and-aft direction and had marginal changes in the left-to-right direction. When the tiller worked at high engine speed, the handle vibrated most violently in the fore-and-aft direction, while the vibrations at the engine cover and handle decreased substantially in each direction, compared with the static conditions. Rotary blades cutting soil increased the damping of the whole machine so as to reduce the vibration at the handle and the engine cover, but the handle vibration was still violent. When the tiller worked, that soil absorbing energies of some frequencies led to the first order unbalanced inertia force of the engine becoming the main reason why handle vibrated intensely.Keywords: mini-tiller, vibration test, time domain analysis, frequency domain analysisDOI: 10.3965/j.ijabe.20160903.1979Citation: Li G, Chen J, Xie H J, Wang S M. Vibration test and analysis of mini-tiller. Int J Agric & Biol Eng, 2016; 9(3): 97－103.